Expression of Conflict Communication in the Discourse of Presidential Election in Lithuania (2019) - Linkevičiūtė, Vilma (Respectus Philologicus, 2020)
The subject matter of the article is different linguistic means of political conflict communication proper to the presidential discourse in Lithuania (2019). The research deals with the conflict communication of the three most popular candidates (according to sociological surveys) – G. Nausėda, S. Skvernelis, and I. Šimonytė. The political discourse of all three candidates is aimed at а positive self-representation; direct or indirect imputations of lack of sustained political commitment from the former president or their political opponents; accusation of pursuing their personal interests, or even making detrimental actions to the state and the society. The most prevalent meaning field in Nausėda’s discourse is welfare – detriment where THEY (former presidents, political parties and their representatives) are granted negative nominations, which are contrasted to positive nominations related to the latter candidate. The most prevailing meaning field in Skvernelis’s discourse is active and responsible state – inactive and irresponsible state which is expressed with the help of two sets of oppositions I – SHE (Grybauskaitė) and I – THEY (Parliamentary opposition and former political majority). The most popular meaning field in Šimonytė’s discourse is welfare – detriment, expressed with the help of I – THEY (members of the Lithuanian Farmers and Greens Union) opposition.